Standard-setting and enforcement of financial reporting standards in South Africa under the old and the new Companies Acts as well as in the European Union - Schmidt, Robert (Stellenbosch : Stellenbosch University, 2015)
Thesis (MAcc)--Stellenbosch University, 2015.